2019
DOI: 10.17352/ojtr.000009
|View full text |Cite
|
Sign up to set email alerts
|

Experience of thyroid surgery at a tertiary care hospital in Karachi, Pakistan

Abstract: Background: Thyroid disorders are common surgical pathology in our part of world. Most commonly encountered complication after thyroid surgery are hypocalcaemia, hoarseness of voice, wound infection, seroma formation and thoracic duct injuries secondary to modifi ed neck dissections. The aim of this study is to share the experience of thyroid surgery at a tertiary care hospital in Karachi, Pakistan with rest of the world. Methodology: The cross sectional descriptive study was conducted in Endocrine unit of Jin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Considering gender epidemiology, females were predominant in our study showed females, males ratio has gaps in 7.65: 1 supported by Altaf et al study represented 5.49:1 female, male ratio, and Vanderpump MPJ study reported a higher prevalence in females [22] [23]. Hegedus et al work also held up our result exhibited frequency higher in the elderly and female [4].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Considering gender epidemiology, females were predominant in our study showed females, males ratio has gaps in 7.65: 1 supported by Altaf et al study represented 5.49:1 female, male ratio, and Vanderpump MPJ study reported a higher prevalence in females [22] [23]. Hegedus et al work also held up our result exhibited frequency higher in the elderly and female [4].…”
Section: Discussionsupporting
confidence: 80%
“…Disease pattern showed euthyroid benign goiter was 142 (82.08%) and euthyroid malignant goiter 31(17.92%) near to Pacini et al study showed the incidence of malignancy of thyroid swelling was 10% Thyroid malignancy in our study showed papillary carcinoma was 93.54%, follicular carcinoma 3.23%, and medullary carcinoma 3.23% near with Altaf et al work showed papillary was 83.1%, medullary 9.9%, and follicular 6.9% [22]. Plauche and Al-Salamah et al also exhibited papillary carcinoma was highest of all other thyroid malignancy 57-89% consistent with our study [39] [40].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Follicular thyroid cancer is the second most common malignancy accounting for 15 of the cases [ 27 ]. Our study showed that papillary thyroid cancer was the most common type followed by follicular thyroid cancer, and this was similar to the UAE [ 28 ], Saudi Arabia [ 29 ], and Yemen [ 30 ], while in Sudan, the most common type of thyroid cancer was follicular thyroid cancer [ 31 ], and in Pakistan, the most type seen was papillary thyroid cancer followed by medullary carcinoma, and follicular thyroid cancer is the third most common thyroid malignancy [ 32 ].…”
Section: Discussionmentioning
confidence: 78%
“…Chronic hypoparathyroidism with unrecovered normal function after six months was reported in 1.4% of cases and found in more extensive type of surgery. 16…”
Section: Discussionmentioning
confidence: 99%